Generation of HLA-Universal iPSC-Derived Megakaryocytes and Platelets for Survival Under Refractoriness Conditions - Ann-Kathrin Börger; Dorothee Eicke; Christina Wolf; Christiane Gras; Susanne Aufderbeck; Kai Schulze; Lena Engels; Britta Eiz-Vesper; Axel Schambach; Carlos A Guzman; Nico Lachmann; Thomas Moritz; et al. (BMC, 2016)
Abstract Platelet (PLT) transfusion is indispensable to maintain homeostasis in thrombocytopenic patients. However, PLT transfusion refractoriness is a common life-threatening condition observed in multitransfused patients. The most frequent immune cause for PLT transfusion refractoriness is the presence of alloantibodies specific for human leukocyte antigen (HLA) class I epitopes. Here, we have silenced the expression of HLA class I to generate a stable HLA-universal induced pluripotent stem cell (iPSC) line that can be used as a renewable cell source for the generation of low immunogenic cell products. The expression of HLA class I was silenced by up to 82% and remained stable during iPSC cultivation. In this study, we have focused on the generation of megakaryocytes (MK) and PLTs from a HLA-universal iPSC source under feeder- and xeno-free conditions. On d 19, differentiation rates of MKs and PLTs with means of 58% and 76% were observed, respectively. HLA-universal iPSC-derived MKs showed polyploidy with DNA contents higher than 4n and formed proPLTs. Importantly, differentiated MKs remained silenced for HLA class I expression. HLA-universal MKs produced functional PLTs. Notably, iPSC-derived HLA-universal MKs were capable to escape antibody-mediated complement- and cellular-dependent cytotoxicity. Furthermore, HLA-universal MKs were able to produce PLTs after in vivo transfusion in a mouse model indicating that they might be used as an alternative to PLT transfusion. Thus, in vitro produced low immunogenic MKs and PLTs may become an alternative to PLT donation in PLT-based therapies and an important component in the management of severe alloimmunized patients.